2011
DOI: 10.1016/j.ijdevneu.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term behavioral effects of exposure to 21%, 40% and 100% oxygen after perinatal hypoxia–ischemia in the rat

Abstract: Until recently, supplementation with 100% oxygen was standard therapy for newborns who required resuscitation at birth or suffered later hypoxic-ischemic events. Exposure to high concentrations of oxygen, however, may worsen oxidative stress induced by ischemic injury. In this study we investigated the short- and long-term behavioral outcomes in rats that had undergone hypoxic-ischemic brain injury on postnatal day 7, followed by 2h exposure to 21%, 40%, or 100% oxygen, compared to normal controls. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Most animal resuscitation studies use a duration of 120 minutes for the duration of the reoxygenation period. 7,8,10,12 We used 30 minutes of resuscitation because this more closely replicates newborn resuscitation in the delivery suite, and allowed comparison with our previous study of hyperoxia in the moderate model. The resuscitation period followed immediately after the end of the insult to allow fast reoxygenation, as may be expected during an emergency resuscitation in the delivery room.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most animal resuscitation studies use a duration of 120 minutes for the duration of the reoxygenation period. 7,8,10,12 We used 30 minutes of resuscitation because this more closely replicates newborn resuscitation in the delivery suite, and allowed comparison with our previous study of hyperoxia in the moderate model. The resuscitation period followed immediately after the end of the insult to allow fast reoxygenation, as may be expected during an emergency resuscitation in the delivery room.…”
Section: Discussionmentioning
confidence: 99%
“…11 A study by Woodworth et al looked at short-and long-term behavioural effects following resuscitation in air, 40%, or 100% oxygen in postnatal day 7 (P7) rats. 12 They found conflicting long-term results for males (improved sensory skills in both oxygen treated groups) and females (worsened motor skills in air and 40% oxygen group). We have also previously studied the effect of resuscitation in 100% oxygen in combination with therapeutic hypothermia in a P7 rat model of moderate HI, and found that resuscitation in 100% oxygen counteracted the effect of therapeutic hypothermia with an increase in brain damage and worsening of reflex performance.…”
Section: Introductionmentioning
confidence: 99%